Role of the cholinergic antiinflammatory pathway in murine autoimmune myocarditis - Leib, Christoph; Göser, Stefan; Lüthje, Dorit; Öttl, Renate; Tretter, Theresa; Lasitschka, Felix; Zittrich, Stefan; Pfitzer, Gabriele; Katus, Hugo; Kaya, Ziya (Circulation research, 2011)
Rationale: - - This study was performed to gain insights into novel therapeutic approaches for the treatment of autoimmune myocarditis. - - Objective: - - Chemical stimulation of the efferent arm of the vagus nerve through activation of nicotinic acetylcholine receptor subtype-7α (α7-nAChR) has been shown to be protective in several models of inflammatory diseases. In the present study, we investigated the potentially protective effect of vagus nerve stimulation on myocarditis. - - Methods and Results: - - A/J mice were immunized with cardiac troponin I (TnI) to induce autoimmune myocarditis. Mice were exposed to drinking water that contained nicotine in different concentrations and for different time periods (for 3 days at 12.5 mg/L; 3 days at 125 mg/L; 21 days at 12.5 mg/L; and 21 days at 125 mg/L after first immunization). TnI-immunized mice with no pharmacological treatment showed extensive myocardial inflammation and fibrosis and significantly elevated levels of interleukin-6 and tumor necrosis factor-α. Furthermore, elevated levels of mRNA transcripts of proinflammatory chemokines (monocyte chemoattractant protein-1, macrophage inflammatory protein-1β, and RANTES) and chemokine receptors (CCR1, CCR2, and CCR5) were found. Oral nicotine administration reduced inflammation within the myocardium, decreased the production of interleukin-6 and tumor necrosis factor-α, and downregulated the expression of monocyte chemoattractant protein-1, macrophage inflammatory protein-1β, RANTES, CCR1, CCR2, and CCR5. In addition, nicotine treatment resulted in decreased expression of matrix metalloproteinase-14, natriuretic peptide precursor B, tissue inhibitor of metalloproteinase-1, and osteopontin, proteins that are commonly involved in heart failure. Finally, we found that nicotine reduced levels of pSTAT3 (phosphorylated signal transducer and activator of transcription 3) protein expression within the myocardium. Neostigmine treatment did not affect the progression of myocarditis. - - Conclusions: - - We showed that activation of the cholinergic antiinflammatory pathway with nicotine reduces inflammation in autoimmune myocarditis. Our results may open new possibilities in the therapeutic management of autoimmune myocarditis.
Gesehen am 15.08.2022